The Effect Methodology of FSH Injection on The Ovulation Rates of Dairy Cattle - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: Tice effect methodology of FSH injection on the ovulation rates of dairy cattle was study. Thirteen lactating cows with body weight between 300 to 400 Kg, superovulated by injection a total of 36 mg FSH Superovulation was started at any day of their cycle between day 9 to 14. The FRI was given twice daily in 12 hours intervals in decreasing doses for 3 and 4 days. Estrumate was injected on day 3 of superovulation (5 th FSH injection) and all donors were artificially inseminated with frozen semen on the onzct of Oestrus, 12 hours and 24 hours afterwith. The embryo were non surgically collected on day seventh. Majority of embryo was in morulla stages